Shahimi M-Studio / Mohd Shahridwan Ramli ... [et al.] - Ramli, Mohd Shahridwan; Taib, Nurulhuda; Ismail, Roziah; Sabdin, Sarimi; Nik Muhammad, Nik Majizaidi; Shaffie, Nor Afiizal; Harun, Nazuha; Wan Norudin, Siti Wan Aminah (2020)
Since the COVID-19 pandemic hits Malaysia and worldwide, education must embrace the digital education approach with limited resources. One of the problems is to produce teaching and learning videos in a short period to fulfill the new norm demand in education. Not all teachers or lecturers are capable to produce a video using a computer. Hence, to ease and assist the educators, Shahimi M-Studio was invented using used cardboard to be a mini-studio and the recording is done by using a smartphone. The teaching process is done by writing on the paper. Video can be made in a shorter time relatively. The objectives of this ministudio are to produce teaching and learning videos in a short period with limited resources, to recycle used cardboard and cheap materials, hence, to join the save nature campaign and to ensure that there are no barriers in education. This innovation is carried out to students at Kelantan Matriculation College batch 2020/2021, the video recorded using Shahimi M-Studio was uploaded to all the provided platforms and receive positive feedbacks from most of the students. The team made a few improvements to the prototype to overcome errors and hope the innovation can provide benefits to educators.